B-mode and doppler ultrasonography of adrenal glands of healthy dogs - Fernandez, S. [UNESP]; Feliciano, M. A.R. [UNESP]; Crivellenti, S. B.; Crivellenti, L. Z.; Simões, A. P.R. [UNESP]; Maronezi, M. C. [UNESP]; Uscategui, R. R. [UNESP]; Capela, C. R. [UNESP]; Gilor, C.; Santana, A. E. [UNESP]; Vicente, W. R.R. [UNESP] (FapUNIFESP (SciELO), 2016)
The aim of this study was to determine the vascular indices of adrenal blood flow in healthy dogs (systolic velocity-SV; diastolic velocity-DV; resistance index-RI). Eighteen dogs (thirty six adrenal) were studied. Physical examination, biochemical profile and dexamethasone suppression test were performed to determine general health status. Echotexture, size, contours and margins, and overall shape of the adrenal gland (right and left) were assessed via ultrasound. By spectral Doppler of the phrenicabdominal artery, the SV, DV, and RI were acquired. Animals did not show alterations in clinical and laboratory examination and suppression of cortisol. Normal homogeneous and echotexture, regular contours and margins and normal shape and size were verified via B mode. Spectral Doppler of the phrenic-abdominal artery showed monophasic-patterned waves and low vascular resistance and systolic peak evident with means values: left adrenal-SV=31.34cm/s, DV=9.54cm/s and RI=0.69; and right adrenal-SV=27.83cm/s, DV=7.71cm/s and RI=0.68. Doppler evaluation of adrenal was easily implemented and may provide base line data in the study, allowing for the use of this technique as a diagnostic tool for diseases of the dog's adrenal.
Keywords: Adrenal glands; Canine; Ultrasound; Vascularization